Whiteboard-based teleconferencing application on mobile devices over existing XMPP servers - Lorenzo, John Bennedict T. (2011)
The need for internet teleconferencing is fueled by businesses which do not have the time and resources to transport all the needed employees located around the world to work on a project or collaborate on an idea. Current solutions to internet teleconferencing include VoIP and video conferencing, e.g. Skype. VoIP permits a natural way of communication through voice but lacks visual information communication. On the other hand, video conferencing requires a lot of bandwidth. The proposed approach uses a shared drawing board, which all collaborators can see in realtime, together with VoIP to provide an intuitive and effective communication medium. Our approach requires less bandwidth than video conferencing and is able to communicate ideas such as ways of solving a circuit problem, collaborating on an interface prototype for a new project, or strategizing a basketball game. Our approach utilizes the touch screen interface of current tablets and smartphones as an intuitive way to draw. The application uses Google's existing XMPP servers, for three reasons: (1) most people already have accounts on them, (2) those accounts have existing contacts, and (3) offload server maintenance to another entity. The system obtained a passing SUS score and a lower than expected MOS.